A Study of the Requirements of p-11B Fusion Reactor by Tokamak System Code. (17th February 2022) - Cai, Jianqing; Xie, Huasheng; Li, Yang; Tuszewski, Michel; Zhou, Hongbin; Chen, Peipei
Abstract: Most tokamak devices including ITER exploit the deuterium-tritium reaction due to its high reactivity, but the wall loading caused by the associated 14-MeV neutrons will limit the further development of fusion performance at high beta. To explore the p- 11 B fusion cycle, a tokamak system code is extended to incorporate the relativistic bremsstrahlung since the temperature of electrons approaches the electron rest energy. By choosing an optimum p- 11 B mix and ion temperature, some representative sets of parameters of the p- 11 B tokamak reactor, whose fusion gain exceeds 1, have been found under the thermal wall loading limit and beta limit when synchrotron radiation loss is neglected. However, the fusion gain greatly decreases when the effect of synchrotron radiation loss is considered. Helium ash also plays an important role in the fusion performance, and we have found that the helium confinement time must be below the energy confinement time to keep the helium concentration ratio in an acceptable range.